The criminal liability for the transmission of the Novel COVID-19 to others in accordance with the Bahraini Legislation (Analytical Study) - Husein Bani-issa, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Since appearance of the new Corona virus (Covid-19) in China, then its spread in Bahrain and all over the world at the beginning of 2020, the Kingdom of Bahrain has faced the pandemic with strict measures, including imposing restrictions on travel, commercial exchanges, closing public places and places of worship. The study aims to identify the punitive confrontation with the spread of epidemics such as the Corona virus in light of the effective Bahraini legislation. Also, adapting the crimes resulting from the transmission of the Corona virus intentional and non-intentional, furthermore sufficiency in providing influential punitive protection for society and individuals, especially in light of the seriousness of this virus and the impact of its spread on all aspects of health life, economic, social and others.